PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS X (AKUNTANSI) SMK ROKAN BAGAN SIAPIAPI TAHUN AJARAN 2015/2016 - Effendi '; Irda Sayuti; Wan Syafii (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of interviews and observations that have been implemented by researchers teachers rarely use model cooperative learning, student learning outcomes and low it can be known from the students who completely individually on the KKM 75 IE 67,64%. Therefore carried out the renovation of the learning by applying cooperative learning to improve the learning outcomes of students in SMK ROKAN Bagansiapiapi. One type of cooperative learning, i.e. Student Teams Achievement Division (STAD). This research was conducted in class X SCIENCE (accounting) SMK Rokan Bagansiapiapi the academic year 2015/2016 to know improvements learn IPA students by applying cooperative learning model type STAD. This research is a research action class is done in two cycles, which consists of planning, implementation, observation and reflection. The data collected in this study is the student learning which consists of absorption, learning, student activities and teacher activities. The data collected using the test and the observation sheet. Absorption based on the value of the post test on cycle I rise on post test 1 is 71.14% (less) become 97.40% (very good) on the post test 2 and in cycle II, the average post test 1 94.53 (very good) became 96.36 (very good) on the post test 2. student learning based on Deuteronomy I cycle daily i.e. 72.12% (less) and cycle II increased to 82.12% (good). Group Award at the cycle I, 2 groups and 2 super group the predicate predicate excellent and good Group 2. In cycle II, all predicate good. Learning activities of students at the time of discussing with the application of cooperative learning model type STAD cycle 1 rise in cycle I, namely 67.87% (less) increased to 82.12% (good) in cycle II. The activity of the teacher in the process of teaching and learning on a cycle I was 87,83%, (good) and cycle II is 95.83% (very good). It can be concluded that the application of the model of the pembelaaran cooperative type STAD can improve the learning results of IPA students class X SCIENCE (accounting) years 2016 2015/Lessons.Key words: Cooperative Learning, Learning Outcomes, Kooperati type of Student Teams achievement award Division (STAD)